(untitled) (Progressive Agriculture, 2016)
Maize is considered as the third most important cereal crop and has more versatile uses in Bangladesh. The study was undertaken to examine the profitability and technical efficiency of maize production as well as to determine the influence of various socio-economic features on farmers land allocation for maize farming in Bangladesh. In doing so, the study utilized the farm-level data collected by the field survey in Lalmonirhat district of Bangladesh. A total number of 60 farmers were selected by using stratified random sampling method among which 36, 20 and 4 farmers were selected under three strata, small, medium and large farmers, respectively. Data were analyzed using simple statistical techniques as well as OLS regression analysis. The comparative analysis among different strata of farmers by this study brought into being that large farmers received higher profit compared to the small and medium farmers. The other results of the study include that maize cultivation helped a lot in improving the nutritional status of the rural people; in creating employment opportunity for them and in increasing household income in the study area. The result of the OLS method suggests that factors like education level, neighbors influence, farm size and higher output price of maize have significant influence upon the choice of farmers land area allocation for maize cultivation in the study area. Based on the findings, this study recommends that proper initiatives must be undertaken by the responsible authority to ensure the efficient use of resources by the maize farmers. Progressive Agriculture 27 (3): 346-354, 2016